The Milltown boys at sixty - Williamson, Howard, author.
1 online resource
Keywords: "The Milltown Boys at Sixty is a story like no other, giving both an insider and an outsider view of the 'Milltown Boys', exploring the nature of an ethnographic relationship based on research about their experiences of the criminal justice system. A group classically labelled as delinquents, drug-takers and drop-outs, the Boys were also, in many different ways, fathers, friends and family men, differentially immersed in the labour market, in very different family relationships and now very differently connected to criminal activity. Williamson has written books capturing their experiences over the fifty years of his continued association with them: about their teenage years; and twenty years later, in middle-age. This book is about them as they pass the age of 60, providing a personal account of the relationship between Williamson and the Boys, and the distinctive - perhaps even controversial - research methodology that enabled the mapping of their lives. It provides a unique and detailed insight into the ways in which the lives of the Milltown Boys that started with such shared beginnings have unfolded in so many diverse and fascinating ways. These accounts will be of interest to the lay reader curious about the way others have managed (or failed to manage) their lives, the professional who works with those living, often struggling, on the wrong side of the tracks, and the academic researching and teaching about social exclusion, substance misuse, criminal justice transitions and the life course"--